How Do Contextual Factors Influence Implementation and Receipt of Positive Youth Development Programs Addressing Substance Use and Violence? A Qualitative Meta-Synthesis of Process Evaluations. Issue 4 (May 2018) - Dickson, Kelly; Melendez-Torres, G. J.; Fletcher, Adam; Hinds, Kate; Thomas, James; Stansfield, Claire; Murphy, Simon; Campbell, Rona; Bonell, Chris
Objective: Positive youth development (PYD) often aims to prevent tobacco, alcohol, and drugs use and violence. We systematically reviewed PYD interventions, synthesizing process, and outcomes evidence. Synthesis of outcomes, published elsewhere, found no overall evidence of reducing substance use or violence but notable variability of fidelity. Our synthesis of process evaluations examined how implementation varied and was influenced by context. Data Source: Process evaluations of PYD aiming to reduce substance use and violence. Study Inclusion Criteria: Overall review published since 1985; written in English; focused on youth aged 11 to 18 years; focused on interventions addressing multiple positive assets; reported on theory, process, or outcomes; and concerned with reducing substance use or violence. Synthesis of process evaluations examined how implementation varies with or is influenced by context. Data Extraction: Two reviewers in parallel. Data Synthesis: Thematic synthesis. Results: We identified 12 reports. Community engagement enhanced program appeal. Collaboration with other agencies could broaden the activities offered. Calm but authoritative staff increased acceptability. Staff continuity underpinned diverse activities and durable relationships. Empowering participants were sometimes in tension with requiring them to engage in diverse activities. Conclusion: Our systematic review identified factors that might help improve the fidelity and acceptability of PYD interventions. Addressing these might enable PYD to fulfill its potential as a means of promoting health.